2015
DOI: 10.1016/j.aquatox.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of charge and surface ligand properties of nanoparticles on oxidative stress and gene expression within the gut of Daphnia magna

Abstract: Concern has been raised regarding the current and future release of engineered nanomaterials into aquatic environments from industry and other sources. However, not all nanomaterials may cause an environmental impact and identifying which nanomaterials may be of greatest concern has been difficult. It is thought that the surface groups of a functionalized nanoparticles (NPs) may play a significant role in determining their interactions with aquatic organisms, but the way in which surface properties of NPs impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 55 publications
4
69
2
1
Order By: Relevance
“…A number of relevant data exist on the toxic impacts of metallic NPs on D. magna (Bondarenko et al 2013;Fan et al 2012;Kahru et al 2008;Pakrashi et al 2013;Dalai et al 2013;Dominguez et al 2015;Mwaanga et al 2014). Several studies reported that AgNPs induced toxicity, uptake, and accumulation in D. magna (Bondarenko et al 2013;Gaiser et al 2011;Stensberg et al 2014;Asghari et al 2012;Hoheisel et al 2012;Zou et al 2014).…”
Section: Agnp Acute Toxicity To D Magnamentioning
confidence: 96%
See 1 more Smart Citation
“…A number of relevant data exist on the toxic impacts of metallic NPs on D. magna (Bondarenko et al 2013;Fan et al 2012;Kahru et al 2008;Pakrashi et al 2013;Dalai et al 2013;Dominguez et al 2015;Mwaanga et al 2014). Several studies reported that AgNPs induced toxicity, uptake, and accumulation in D. magna (Bondarenko et al 2013;Gaiser et al 2011;Stensberg et al 2014;Asghari et al 2012;Hoheisel et al 2012;Zou et al 2014).…”
Section: Agnp Acute Toxicity To D Magnamentioning
confidence: 96%
“…A number of biochemical biomarkers were studied in Daphnia magna after acute exposure to different pollutants (Jemec et al 2008; Barata et al 2005;Toumi et al 2015;Diamantino et al 2000). The information on biochemical responses in D. magna exposed to different ENPs are still scarce, despite the requirements for risk assessment of the potential impact of ENPs on the aquatic environment (OECD 2004;Dominguez et al 2015;Zou et al 2014;Mwaanga et al 2014;Strużyński et al 2014). The aquatic crustacean D. magna has been recognized as first choice in ecotoxicological tests on nanomaterials (Baun et al 2008;Kahru et al 2008).…”
Section: Responsible Editor: Thomas Hutchinsonmentioning
confidence: 99%
“…The results presented here may be of relevance for explaining the molecular origin of nanoparticle-specific and dose-dependent decreases in the viability of Shewanella 44 and Daphnia 45,46 exposed to the same nanoparticle formulations (ligands and size and core composition) for which lipid corona formation is reported here. Ongoing efforts focus, therefore, on uncovering possible links between lipid corona formation and oxidative stress in daphnid tissues 47 as well as the alteration of the expression of individual genes in the form of RNA production, specifically those associated with metabolism, reproduction, and growth. 45 In the long term, we believe that our approach for studying the nano-bio interface, whereby understanding the nanomaterial and its coating along with the biological membrane is considered equally important, will increase our ability to predict the impact that the increasingly widespread use of engineered nanomaterials in industrial applications and consumer products has on the fate of these materials once they enter the environment [48][49][50][51] and the food chain, which many of them eventually do.…”
Section: Nanoparticle-vesicle Suspensions Form Aggregated Superstructmentioning
confidence: 99%
“…5 No general trends were reported for other properties such as hydrophilicity of the stabilizers or presence/absence of certain reactive groups in the coatings (Kim et al, 2013;Levard et al, 2012). In addition, the stabilizer itself changed the toxicity as well as the mode of action of the investigated nanoparticles in other experimental studies (Baumann et al, 2014a;Bozich et al, 2014;Dominguez et al, 2015).…”
Section: Introductionmentioning
confidence: 98%